Efektivitas kelompok diskusi tutorial problem based learning di Fakultas Kedokteran Universitas Sam Ratulangi - Pioh, Virgin Enjel; Mewo, Yanti; Berhimpon, Siemona (Universitas Sam Ratulangi, 2016)
Abstract: The Faculty of Medicine, Sam Ratulangi University has applied the Problem Based Learning (PBL) method in which the tutorial group discussion is the center in this learning method. The purpose of PBL is to improve the studentsâ€™ problem solving skill which is essential for the students who are going to be professional medical practitioners in the future. Therefore, the effectiveness of the tutorial group discussion of PBL must be implemented in order to achieve the learning goalsThe cognitive aspect is related to the studentsâ€™ knowledge whilst the motivational aspect is dealing with the factors which enforce the students to perform better in learning. This study aimed to obtain the effectiveness of the tutorial group discussion of PBL at the Faculty of Medicine, Sam Ratulangi University. This study employed the Tutorial Group Effectiveness Instrument (TGEI) questionnaire which included the motivational aspects, cognitive aspect, and demotivational aspect. This TGEI (Indonesian language version) questionnaire was distributed to 40 students from class of 2015 who fulfilled the inclusive criteria before the seminar (the plenary) of Biophysics module. The results showed that the effectiveness of the tutorial group discussion of PBL was good by the majority of students (95%). In particular, the cognitive aspect, motivational aspect and demotivational aspect were rated good by the students for about 87.5%, 92.5% and 70%, respectively. Conclusion: In general, the effectiveness of the tutorial group discussion of PBL at the Faculty of Medicine, Sam Ratulangi University was good. Keywords: tutorial group, effectiveness, collaborative, TGEIÂ Abstrak: Fakultas Kedokteran Universitas Sam Ratulangi telah menerapkan metode pembelajaran Problem based learning (PBL). Kelompok diskusi tutorial menjadi inti dalam PBL yang bertujuan untuk meningkatkan kemampuan mahasiswa dalam memecahkan masalah. Sebagai mahasiswa calon profesi dokter, kemampuan memecahkan masalah menjadi modal utama dalam menjalani profesi dimasa depan. Penelitian ini bertujuan untuk mengetahui efektivitas kelompok diskusi tutorial PBL di Fakultas Kedokteran Universitas Sam Ratulangi. Penelitian ini menggunakan kuesioner Tutorial Group Effectiveness Instrument (TGEI) yang didalamnya mencakup aspek motivasi, aspek kognitif, dan aspek demotivational. Kuesioner TGEI (versi bahasa Indonesia) dibagikan kepada 100 mahasiswa angkatan 2015 yang masuk kriteria inklusi sebelum seminar (pleno) Modul Biofisika. Hasil penelitian menunjukkan bahwa, sebagian besar (95%) mahasiswa memberikan pernyataan dengan penilaian terhadap efektivitas kelompok diskusi tutorial PBL ialah baik. Bila dilihat dari ketiga aspek yang dijadikan dasar penilaian efektivitas, 87,5% mempunyai penilaian baik untuk aspek kognitif, 92,5% mempunyai penilaian baik untuk aspek motivasi, dan 70% mempunyai penilaian baik untuk aspek demotivational. Simpulan: Secara umum, efektivitas kelompok diskusi tutorial PBL di Fakultas Kedokteran Universitas Sam Ratulangi ialah baik.Kata kunci: kelompok tutorial, efektivitas, kolaboratif, TGEI